2018
DOI: 10.1016/j.hjc.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis on the correlation between admission hyperglycemia and myocardial infarct size on CMRI

Abstract: The main finding of our analyses is that the size of myocardial infarct detected on CMR is positively correlated to admission hyperglycemia in patients with AMI. The clinical importance of this study lies in the accurate assessment of prognostic value of admission glucose, which would help clinicians in risk stratification and treatment decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…There is controversy about whether elevated blood glucose on admission is merely an expression of severe disease or whether hyperglycemia is causally associated with serious consequences such as complications or death [ 23 25 ]. There are several eligible pathophysiological mechanisms potentially mediating a causal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…There is controversy about whether elevated blood glucose on admission is merely an expression of severe disease or whether hyperglycemia is causally associated with serious consequences such as complications or death [ 23 25 ]. There are several eligible pathophysiological mechanisms potentially mediating a causal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, in patients with AHG, the proportion of low TIMI flow scores was higher than that in patients with normal blood glucose levels after PCI [16]. Infarct size was larger [17], and the incidence rates of malignant arrhythmia [18] and cardiac shock [19] were also higher in patients with AHG, especially in non-DM patients than in those without AHG [16]. In the current study, CK-MB, cardiac troponin I, and MYO levels were higher in the severe hyperglycemia group of non-DM patients with AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Yacov et al reported that admission hyperglycemia was an independent risk factor for acute kidney injury in nondiabetic ST-segment elevation myocardial infarction patients undergoing primary PCI [ 14 ]. Stella et al performed a meta-analysis on the relationship between admission hyperglycemia and myocardial infarct size using cardiovascular magnetic resonance imaging (CMRI) and found that the size of myocardial infarct detected on cardiovascular magnetic resonance positively correlated with admission hyperglycemia in patients with acute myocardial infarction [ 15 ]. Ozge et al reported that elevated admission BG level attenuated the coronary collateral flow in patients with ST-elevation myocardial infarction [ 16 ].…”
Section: Discussionmentioning
confidence: 99%